Comparative Study of Abdominal Wall Closure Method – Hughes Technique versus Conventional Mass Closure in Reducing Incisional Hernia - Kafeel, Urwah; Imtiaz, Khurram; Butt, Muhammad Sulman; Mohammad Saad,; Rafia Yaseen,; Muhammad Sufyan, (Indus Journal of Bioscience Research, 2025)
Background: Laparotomy procedures often result in an incisional hernia. There are several methods developed to lessen the chances of incisional hernia after laparotomy. Hughes is an improved method compared to conventional mass closure. But it is not routinely practiced due to a scarcity of evidence in the local population. Objective: To compare the outcome of abdominal wall closure by Hughes technique versus conventional mass closure after laparotomy. Study Design: Randomized controlled trial. Place and Duration: Department of Surgery, Lahore General Hospital, from December 2022 to June 2023. Material and Methods: There were 100 individuals undergoing laparotomy enrolled. Consent was obtained and demographics were noted. Patients were randomly assigned to two groups. Closure was achieved in group A through the use of the Hughes technique. In group B, closure was done by using conventional mass closure technique. Outcomes were noted and analyzed in SPSS version 25. Results: Patients undergoing the Hughes technique, mean age was 46.18 ± 10.48 years. In Conventional mass closure group, mean age of patients was 39.98 ± 9.59 years. In the Hughes technique group, there were 36 (72%) males and 14 (28%) females. Patients undergoing conventional mass closure, there were 25 (50%) males and 25 (50%) females. The mean suture time was 14.44 ± 2.32 minutes with Hughes technique and 13.62 ± 2.06 minutes with conventional method (p>0.05). Wound infection was noted in [4 (8%) vs. 12 (24%), p<0.05]. But wound dehiscence and pain as almost similar in both groups (p>0.05). Incisional hernia developed in 14 (28%) cases with the Hughes technique, while in 27 (54%) cases with conventional mass closure (p<0.05). Conclusion: Hughes technique is superior to conventional mass closure in preventing the development of incisional hernia after surgery, making it more effective and beneficial.